ANALISIS KOMPETENSI PUSTAKAWAN BERBASIS LOWONGAN PEKERJAAN - Silaen, Yoseva (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
This research is based on the author's curiosity about the competencies of Library and Information Science graduates needed in the world of work. One way to find out is to conduct research on job vacancies for the field of Library and Information Science. The library vacancies came from the Facebook group Lowongan Pustakawan which was formed by the author himself since mid-2014 which until 2022 had 12,384 active members. After going through several established categories, there were 363 librarian vacancies as samples in this study. 4 vacancy contributors were found, they are: school libraries, college libraries, special libraries and public libraries. All four mentioned several variations of job titles needed to handle tasks in the library. There are 116 criteria listed in the 363 librarian vacancies. The 116 criteria are classified into 12 competencies, after ranking, the most frequently listed competencies are personality competencies, followed by educational and information technology competencies. This study recommends several things, one of which is that there should be further research to examine competencies specifically at each level of competency in Library and Information Science education.